Downregulation of ITGβ3 in colon adenocarcinoma reveals poor prognosis by affecting genome stability, cell cycle, and the tumor immune microenvironment - Zhao, Lei; Ma, Xiaoting; Li, Guangxin; Zhao, Pengfei; Lin, Haishan; Ma, Yingjie; Li, Huihui; Yu, Jing (Frontiers in Oncology, 2023)
Abnormal expression of integrin subunit Beta 3 (ITGβ3), a gene-encoding protein, is related to the occurrence and development of cancers. The biological role of ITGβ3 in colon cancer (COAD) remains to be determined. We analyzed the mRNA expression,miRNA expression and clinical data of colon adenocarcinoma in the TCGA database, and obtained ITGβ3 mRNA and miRNAs related genes. Based on relevant known gene expression databases such as cBioPortal, LinkedOmics, TIMER, UALCAN, DAVID and Oncomine, we analyzed ITGβ3 and its correlations with immune-related genes and ITGα genes, screened the important hub genes. The ITGβ3 expression in COAD tumor tissues is significantly down-regulated in comparison with paracancerous tissues. Low ITGβ3 expression in tumor tissues was considerably associated with poor overall survival of COAD patients. In multivariate analysis, stage IV and ITGβ3 low expression were independent prognostic factors. The overall survival of COAD patients with high ITGβ3 expression compared with low ITGβ3 expression was significantly shorter. Gene Ontology (GO) showed that DEGs were significantly enriched in leukocyte migration, cell adhesion, extracellular matrix (ECM) organization, plasma membranes, cell surface, exosomes, protein binding, protease binding, receptor activity. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that the DEGs were mainly enriched in ECM-receptor interaction, focal adhesion, and the PI3K-Akt signaling pathway. Protein-protein interaction network analysis reveals the hub gene and the seed gene of the key module modules related to ITGβ3. ITGβ3 expression was significantly correlated with tumor purity and with the infiltration level of dominant immune cells. Correlation analysis between ITGβ3 and ITGα genes showed that three ITGα members with the highest correlations.These findings indicate that ITGβ3 down-regulation in COAD may profoundly affect RNA splicing, genome stability, and multiple steps of the cell cycle, and is related to the prognosis of colon adenocarcinoma patients.